2014
DOI: 10.17843/rpmesp.2013.301.154
|View full text |Cite
|
Sign up to set email alerts
|

Síntomas respiratorios causados por el uso del electrocauterio en médicos en formación quirúrgica de un hospital de México

Abstract: Con el objetivo de determinar la frecuencia de síntomas respiratorios entre los residentes de especialidades quirúrgicas expuestos al humo del electrocauterio, se realizó un estudio transversal durante el mes de febrero de 2012. Se incluyeron 50 médicos residentes del tercer año, de diferentes especialidades quirúrgicas, de un hospital de tercer nivel perteneciente al Instituto de Seguridad y Servicios Sociales de los Trabajadores del Estado ubicado en Jalisco, México. La selección de sujetos fue no probabilís… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 3 publications
0
13
0
2
Order By: Relevance
“…Resident doctors working in surgical clinics where they are exposed to surgical smoke had a higher prevalence of respiratory signs and symptoms, such as: foreign body sensation in the throat, burning in the pharynx, nausea and nasal congestion. (1) Another study with nurses and physicians found a higher prevalence of headache, irritation of the eyes, cough and burning throat, besides the perception of a bad smell left by the surgical smoke in the operating rooms. (14) Surgical smoke acts cumulatively in the human body (5) .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Resident doctors working in surgical clinics where they are exposed to surgical smoke had a higher prevalence of respiratory signs and symptoms, such as: foreign body sensation in the throat, burning in the pharynx, nausea and nasal congestion. (1) Another study with nurses and physicians found a higher prevalence of headache, irritation of the eyes, cough and burning throat, besides the perception of a bad smell left by the surgical smoke in the operating rooms. (14) Surgical smoke acts cumulatively in the human body (5) .…”
Section: Introductionmentioning
confidence: 99%
“…Electrocauterization reduces surgical time and bleeding, facilitating the visualization of the operating field (1) On the other hand, incomplete combustion during the cauterization of tissues and blood vessels generates surgical smoke, which is composed of water vapor and biological and chemical compounds that may be carcinogenic. (2,3) Among the biological compounds, studies have revealed the presence of the hepatitis B virus and the human papillomavirus in surgical smoke; however, these agents have not been confirmed as responsible for the development of diseases in the workers exposed to this smoke.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of electrocautery decreases intraoperative bleeding and improves visibility during surgery (1) , but the smoke produced because of its use can harm the health of workers.…”
Section: Introductionmentioning
confidence: 99%
“…These chemicals may trigger genetic mutations (6) and cancer (7) in the human body. In addition to mutation and cancer, the particles in the electrocautery smoke can be inhaled and retained in the workers' respiratory tract, causing various respiratory signs and symptoms, including foreign body sensation in the throat, burning pharyngeal, nausea and nasal congestion (1) . It can also cause headache and eye irritation (2) .…”
Section: Introductionmentioning
confidence: 99%